2016
DOI: 10.1016/j.jphs.2015.07.021
|View full text |Cite
|
Sign up to set email alerts
|

3,4,5-Trimethoxycinnamic acid, one of the constituents of Polygalae Radix exerts anti-seizure effects by modulating GABAAergic systems in mice

Abstract: Polygalae Radix is an important medicinal plant that is widely used in most of Africa. 3,4,5-Trimethoxycinnamic acid (TMCA) is one of the constituents of Polygalae Radix. Until now, the mechanisms involved in the anti-seizure property of TMCA are still unclear. We examined the anti-seizure effect of TMCA. TMCA administered at doses of 5, 10 and 20 mg/kg and evaluated anti-seizure effects by maximal electroshock (MES) and pentylenetetrazol (PTZ) models in mice. TMCA administered at doses of 10 and 20 mg/kg sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…After activation, NF-κB regulates the expression of genes such as those encoding the inflammatory cytokines TNF-α, IL-1, and IL-6 that can directly or indirectly affect microvascular endothelial cells or blood cells to mediate their interaction, which leads to the dysfunction of microcirculation, endothelial cell, and tissue injury. 18 …”
Section: Resultsmentioning
confidence: 99%
“…After activation, NF-κB regulates the expression of genes such as those encoding the inflammatory cytokines TNF-α, IL-1, and IL-6 that can directly or indirectly affect microvascular endothelial cells or blood cells to mediate their interaction, which leads to the dysfunction of microcirculation, endothelial cell, and tissue injury. 18 …”
Section: Resultsmentioning
confidence: 99%
“…In Gunia’s study, it was confirmed that the cinnamic acid derivatives have anticonvulsant activity and their study clarifies a new way to discover new potential anticonvulsants [ 18 ]. In 2015, a cinnamic acid, 3,4,5-trimethoxycinnamic acid, the main active ingredient isolated from P. tenuifolia , has been found to display anticonvulsant effect [ 19 ]. Animal models have made great contributions to the treatment of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Recent pharmacological studies have suggested that PT and its extracted fractions have significant effects regarding neuroprotection (Wang et al 2019), anti-amnesia (Zhang et al 2008), anti-depressant properties (Cao et al 2018) and relieving the symptoms of extreme fear in rats (Shin et al 2018). The main chemical components in PT include triterpenoid saponins, oligosaccharide esters and organic acids, of which oligosaccharide esters and organic acids are beneficial for the central nervous system (Liu et al 2015;Chen et al 2016). Sibiricose A5 (A5), sibiricose A6 (A6), 3,6 0 -disinapoyl sucrose (DSS) and tenuifoliside A (TFSA) are representative oligosaccharide esters in PT, while 3,4,5-trimethoxycinnamic acid (TMCA) is a representative organic acid, which showed anti-seizure (Chen et al 2016), antistroke (Li et al 2017), anti-inflammatory (Kim et al 2013), neuroprotective (Liu et al 2015) and anti-depressant-like effects (Hu et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The main chemical components in PT include triterpenoid saponins, oligosaccharide esters and organic acids, of which oligosaccharide esters and organic acids are beneficial for the central nervous system (Liu et al 2015;Chen et al 2016). Sibiricose A5 (A5), sibiricose A6 (A6), 3,6 0 -disinapoyl sucrose (DSS) and tenuifoliside A (TFSA) are representative oligosaccharide esters in PT, while 3,4,5-trimethoxycinnamic acid (TMCA) is a representative organic acid, which showed anti-seizure (Chen et al 2016), antistroke (Li et al 2017), anti-inflammatory (Kim et al 2013), neuroprotective (Liu et al 2015) and anti-depressant-like effects (Hu et al 2010). To date, several pharmacokinetic studies about the active components of PT have been reported.…”
Section: Introductionmentioning
confidence: 99%